Pancasila and Communism Perspectives on Islamic Thought - Hidayat, Syamsul; Shobron, Sudarno; Muthoifin; Casedi, Edi (International Journal of Psychosocial Rehabilitation, 2020)
Pancasila is the cornerstone of the Republic of Indonesia, belief in the Almighty God, the fair and humane civilization, the peace of Indonesia, equality, and guided by the knowledge of knowledge of freedom and social justice for all Indonesians. Belief in the Almighty God is the basic premise of the five established precepts. This rule allows the people of the Republic of Indonesia to be godless. In reality, however, Indonesia’s history and recognition of the Indonesian Communist Party in the elections This study attempted to sit communism inside Pancasila’s philosophy and whether he has any room in it. This study is intended to address the question in the hope that people consider and appreciate the principles of Communism in their domestic life. Be a kind of historical-philosophical literary qualitative analysis. Results showed that communism study is contrary to the values of Pancasila, which are the cornerstone of the Republic of Indonesia, from the perspective of philosophy, politics, socio-economics. Thus, there is no room in Pancasila because of the above teachings and philosophy of communism. Since anything cannot be coordinated and balanced in breach. Since ideology is contradictory and has no place in the basic state and nation of Indonesia, it can and should be fair to assassinate Indonesia’s Communist state "and to make Russia a complice" where that theory is not worth living fertile motherland ever betrayed by the PKI.